The Linguistic Differences and its Effects in Interpreting the Problem of Hadith through his saying (May Allah’s Peace and Blessing be upon him): “The dead will be tormented by the wailing of his family over him”: An Applied Study - Dirami, Zakaria' Mumad (Journal of Humanities & Social Sciences, 2022)
This research dealt with the answer to the supposed problem of the hadith (The dead will be tormented by the wailing of his family over him), through the phenomenon of linguistic differences, as it was reached by differentiating between the word (torment) contained in the hadith and the immediate meaning of the word (punishment) by some who find the hadith problematic, in an attempt to establish linguistic differences as a path of interpretation and reconciliation between hadiths that seem to be supposed contradictory, with an explanation of the methods of revealing these differences, and the types of relationships between the words. The research found some important results: First: The difference between the word (torment) mentioned in the hadith “The dead is tormented by the wailing of his family over him” and the immediate meaning of the word (punishment) by some who find the hadith problematic. Second: The relationship between (torment and punishment) is a general and specific relationship, so every punishment is a torment, and not every torment is a punishment. Third: The difference between the two words was arrived at by different means, the most important of which are: rationality, textual evidence, usage, and consideration of the morphological forms of the two words. Fourth: Consideration of linguistic differences as a path of interpretation and reconciliation of seemingly contradictory texts. Fifth: Among the reasons for the confusion of hadiths are: linguistic weakness, and lack of knowledge of the subtle differences between words.